Disabilitas dan Keselamatan Pasien : Studi Literatur - Dhamanti, Inge; Larasati, Andriyani (LPPM Hang Tuah Pekanbaru, 2024)
Improving the safety of vulnerable patient groups in health care is a priority. Patients with disabilities are among the most vulnerable groups. Persons with disabilities have more complex and extensive healthcare needs than non-disabled patients. This literature review aims to identify the types of patient safety incidents that can be used in patients with disabilities. The keywords